A large animal model for CNGB1 autosomal recessive retinitis pigmentosa. - Paige A Winkler; Kari J Ekenstedt; Laurence M Occelli; Anton V Frattaroli; Joshua T Bartoe; Patrick J Venta; Simon M Petersen-Jones (PLoS ONE, 2013)
Retinal dystrophies in dogs are invaluable models of human disease. Progressive retinal atrophy (PRA) is the canine equivalent of retinitis pigmentosa (RP). Similar to RP, PRA is a genetically heterogenous condition. We investigated PRA in the Papillon breed of dog using homozygosity mapping and haplotype construction of single nucleotide polymorphisms within a small family group to identify potential positional candidate genes. Based on the phenotypic similarities between the PRA-affected Papillons, mouse models and human patients, CNGB1 was selected as the most promising positional candidate gene. CNGB1 was sequenced and a complex mutation consisting of the combination of a one basepair deletion and a 6 basepair insertion was identified in exon 26 (c.2387delA;2389_2390insAGCTAC) leading to a frameshift and premature stop codon. Immunohistochemistry (IHC) of pre-degenerate retinal sections from a young affected dog showed absence of labeling using a C-terminal CNGB1 antibody. Whereas an antibody directed against the N-terminus of the protein, which also recognizes the glutamic acid rich proteins arising from alternative splicing of the CNGB1 transcript (upstream of the premature stop codon), labeled rod outer segments. CNGB1 combines with CNGA1 to form the rod cyclic nucleotide gated channel and previous studies have shown the requirement of CNGB1 for normal targeting of CNGA1 to the rod outer segment. In keeping with these previous observations, IHC showed a lack of detectable CNGA1 protein in the rod outer segments of the affected dog. A population study did not identify the CNGB1 mutation in PRA-affected dogs in other breeds and documented that the CNGB1 mutation accounts for ~70% of cases of Papillon PRA in our PRA-affected canine DNA bank. CNGB1 mutations are one cause of autosomal recessive RP making the CNGB1 mutant dog a valuable large animal model of the condition.